Analysis of combustion of methane and hydrogen–methane blends in small DI SI (direct injection spark ignition) engine using advanced diagnostics. (1st August 2016) - Di Iorio, Silvana; Sementa, Paolo; Vaglieco, Bianca Maria
Abstract: In the last years, even more attention was paid to the alternative fuels that allow reducing the fuel consumption and the pollutant emissions. Gaseous fuels like methane and hydrogen are the most interesting in terms of engine application. This paper reports a comparison between standard gasoline fuel, methane and different methane/hydrogen blends in a transparent single-cylinder DI SI (direct injection spark ignition) engine representative of the small displacement gasoline engine for automotive application. Engine performance and regulated exhaust emissions were evaluated under steady state condition at 2000 rpm – full load, and stoichiometric condition. 2D-digital cycle resolved imaging measurements were performed from the start of injection to the end of combustion. They allowed the characterization of the gaseous and liquid injection and the flame propagation, in terms of the mean radius and velocity. The combustion promotion due to the hydrogen addition and its contribution to the reduction of the pollutant formation were estimated. Highlights: Use of gaseous fuels to reduce the fuel consumption and the pollutant emissions. Analysis of gaseous direct injection into the combustion chamber. Comparison between combustion of gasoline fuel, methane and methane/hydrogen blends. Combustion promotion due to the hydrogen addition and reduction of the pollutant formation.